The Influence of Career Developments to The Work Motivation of Employees of Health Polytechnic of Surabaya - Siti Surasri 3, Mamik1, Murtini2, (International Journal of Scientific Research and Management (IJSRM), 2016)
The purposes of this study are to analyze and to examine the influence of education, training, promotion, and mutation at Health Polytechnic of Surabaya to employees work motivation. The data collecting method is the field observation, by distributing questionnaires and interviewing 203 employees as samples. Then, the data was processed and analyzed by using Multiple Linear Regression Analysis method.By F-test, it can be concluded that education, training, promotion, and mutation simultaneously influence employees work motivation. By T-test, each independent variable, i.e. education, training, promotion, and mutation, has partial influence to employees work motivation. Also, promotion is a dominant variable for employees work motivation.